IMPROVING BIOSTATISTICS UNDERSTANDING USING THE MIND MAPPING LEARNING MODEL - Agus Riyanto; Syukri Hamzah; Hadiwinarto Hadiwinarto (Jurnal Scientia, 2023)
This study aims to increase students' understanding of the biostatistics course on T-Test material at STIKes Bhakti Husada Bengkulu by using the Mind Map learning method. This study aimed to determine the increase in students' creative thinking skills using the Mind Mapping method approach. This research method is Pre and Post Experiment. The research population is nursing study program students. The results showed that the use of the mind-mapping approach could improve students' creative thinking abilities. understanding, it appears that students are more able to develop ideas and ideas to solve problems using mind mapping, so it can be concluded that there is an influence of the mind mapping method on increasing comprehension of the t-test material biostatistics course.